Eixos temáticos do ensino religioso na obra de Inês Carniato: uma análise nos livros didáticos da coleção ensino religioso fundamental - Silva, Maria da Penha Lima da (2018)
The experience as a professor of Religious Education (ER, for the Portuguese abbreviation) aroused the interest in researching how the thematic axes of ER, “Religious” “Culture and tradition”, “Sacred Scripture or Oral Traditions”, “Theologies”, “Rites” and “Ethos” are expressed in the didactic collection of ER by Inês Carniato (2010). My main objective is: to analyze thematic axes of the PCNER that are present on the ER didactic books collection; my specific objectives are: to reflect on the curricular aspects of 5 thematic axes of the ER Culture and Tradition, Sacred Scripture and/or Oral Traditions, Theologies; Ethos and Rites; to present the importance of the ER didactic books in the current curricular policies corroborated in the ER professor formation; to analyze and to catalog in the types of sources presented in the didactic books by Inês Carniato the factors that contribute to the promotion of interreligious dialogue, regarding religious cultural diversity and the orientation for the culture of peace. In this research we adopt, the following procedures, it is a bibliographical research focused in the discourse analysis. A qualitative analysis of data (68 fotographs – texts, statements, images and exercises) consolidated in a first part, descripted, as the author systematized textual elements of the work, the other part, reflective, we emphasized the interpretation of the data based in the literature. As an objective research we use, three didactic books - of 6th grade, 7th grade and the 8th grade of high school, by Inês Carniato authorship. In the first chapter, we will present the historic periods of ER in Brazilian education and the importance of each thematic axis of ER. In the second chapter, a brief historical overview of the ER didactic book and his contribution as a didactic subsidy in the context of Education and Science of Religions. In the third chapter, we will make an analysis of the mentioned books, quoting examples of determined pages of the collection where those ER thematic axes are expressed. It is so, determined pages of the collection, express on certain illustrations, fragments and exercises the idea of a transcendent (a single God in all religions), however they have brought a wide diversity of beliefs and spiritualties throughout the contents